A regra da oitava como ferramenta de análise harmônica - Santos, André dos (2021)
Many studies are being carried out on musical pedagogy from the 17th to the 19th century, opening the ways of understanding the repertoire of these centuries. One of the subjects about these researches is the Octave Rule as a practical musical learning tool. The Rule of Octave brings with it new insights into 17th century harmonic grammar, and possible developments throughout the 18th and 19th centuries. 20th and 21st century harmony manuals do not cite the Rule of Octave as a possible interpretation of harmonic analysis. The present work aims to make a simple comparison between Neapolitan Master Fedele Fenaroli's Rule of Octave; as basic rules for the movement of the bass, with Neapolitan Master Giovanni Furno, and the harmonic examples of the common practice repertoire labeled by Walter Piston.